2015
DOI: 10.1038/onc.2015.342
|View full text |Cite
|
Sign up to set email alerts
|

Increased TEAD4 expression and nuclear localization in colorectal cancer promote epithelial–mesenchymal transition and metastasis in a YAP-independent manner

Abstract: Dysregulation of the Hippo pathway occurs in a variety of cancers and often correlates with a poor prognosis. To further explore the potential role of Hippo pathway dysregulation in tumor development and progression, we investigated its downstream transcription factor TEAD4 in colorectal cancer (CRC). Increased expression and nuclear localization of TEAD4 were found in a significant portion of CRC tissues, in association with metastasis and a poor prognosis. In CRC cells, TEAD4 knockdown induced the mesenchyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
125
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(133 citation statements)
references
References 38 publications
7
125
1
Order By: Relevance
“…We have also revealed that E6-mediated upregulation of A3B is primarily caused by increased levels of TEAD1/4. A3B and TEAD1/4 are reported to be upregulated in various types of human cancer, and each has been proposed to play important roles in carcinogenesis (5)(6)(7)(8)(9)(28)(29)(30)(31)(32). This study thus establishes a novel transcriptional link between these oncogenic factors.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…We have also revealed that E6-mediated upregulation of A3B is primarily caused by increased levels of TEAD1/4. A3B and TEAD1/4 are reported to be upregulated in various types of human cancer, and each has been proposed to play important roles in carcinogenesis (5)(6)(7)(8)(9)(28)(29)(30)(31)(32). This study thus establishes a novel transcriptional link between these oncogenic factors.…”
Section: Discussionmentioning
confidence: 72%
“…Of particular interest, TEAD4 is overexpressed in several human cancers, such as gastric, breast, and colorectal cancers, and the expression levels of TEAD4 correlate with poor survival of cancer patients (20,(29)(30)(31). Whether such TEAD4 upregulation leads to A3B upregulation in these cancers, thereby contributing to cancer evolution and malignancies, warrants further investigation using cell culture models and clinical specimens.…”
Section: Figmentioning
confidence: 99%
“…While prior studies have indicated TEAD4 driving previously identified YAP/TEAD targets in neuroblastoma cells (62, 80), these studies were performed in MYCN WT cells, further confirming that different regulatory mechanisms are at play in MYCN Amp versus MYCN WT cells. Interestingly, studies in mammary tumors have shown that MYC represses YAP/TAZ activity, while also showing that MYC induction decreases binding of YAP/TAZ to its bona fide targets, CTGF and CYR61, but not of TEAD4 (81); additional studies have shown YAP/TAZ-independent regulatory activity of TEAD4 (82). In contrast to the canonical view that TEAD4 lacks independent transcriptional activation (83), TEAD4 was also recently reported to have a transcriptional activation domain, supporting transcriptional regulation independent of the YAP/TAZ DNA binding domain (84).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have emphasized the role of YAP/TAZ amplification and hyperactivity in various cancers [66], however increased TEAD expression and activity, both dependent and independent of YAP/TAZ, have also been implicated in the progression of several solid tumors [7] (Table 1). High TEAD expression levels are seen in prostate, colorectal, and breast cancers and, concordantly, are an indicator of poor clinical outcome [6771]. In breast cancer cells, induction of epithelial to mesenchymal transition (EMT) resulted in upregulation of TEAD2 and a marked increase in YAP/TAZ nuclear accumulation despite decreases in overall YAP/TAZ protein levels [70].…”
Section: Tead Regulation In Cancersmentioning
confidence: 99%